Annotating the Everyday in a Modernist Scholarly Edition. Issue 1 (February 2020) - Thomson, Tara
Abstract : This article interrogates current approaches to the annotation of scholarly editions in order to reframe annotation practice within an emerging 'new modernist editing'. Using the Broadview edition of Dorothy Richardson's The Tunnel as a case study to reflect on the particular challenges of annotating a modernist text for a particular audience, I explore the problems that emerge from the explanation/interpretation dichotomy that commonly frames annotation practice. While this paper does not devise a prescriptive method for scholarly annotation, its aim instead is to refine our conceptions of the purpose and nature of explanatory notes, by putting them into conversation with contemporary literary theory, and particularly recent approaches to modernism situated in the post-critical turn.